STUDI KUAT TEKAN BAMBU TALI DAN BAMBU AMPEL AKIBAT SERANGAN RAYAP - Deden Wiguna; Bachtiar, Gina; Murtinugraha, R. Eka (Jurnal Pendidikan Teknik dan Vokasional, 2020)
This study aims to determine how the compressive strength of bamboo rope and bamboo Ampel due to termite attack. Where the research was conducted in the Laboratory Test Material Arboretum State University of Jakarta and Bogor Institute of Agriculture in October 1, 2016 - January 30, 2017. This research method using bamboo direct compressive strength testing in the laboratory. In the present study used two types of bamboo, the bamboo rope and bamboo Ampel totaling 40 samples. The total sample of each type of bamboo has the number of 20 samples. According to the position at the base and middle of each totaling 10 samples. For each position there are two treatments, bamboo fed and not fed termites, which amounted to 5 samples. Research conducted compressive strength based on ISO 22 157: 2004. The results showed that the value of the average compressive strength of bamboo and bamboo Ampel rope at the base position and center fed termites decreased from bamboo which is not fed termites. At the base of bamboo straps that are not fed termites of 54.688 kN / cm2.While at the base of bamboo rope that is fed termites of 50.729 kN / cm2.In the central part of bamboo straps that are not fed termites of 54.532 kN / cm2.While on the bamboo rope is fed termites central part of 53.583 kN / cm2.At the base of bamboo Ampel termites were not fed for 51 096 kN / cm2.While at the base of bamboo Ampel were fed termites of 47.084 kN / cm2.In the mid-section of bamboo Ampel not fed termites of 45.559 kN / cm2.While on bamboo Ampel the center that is fed termites of 37.702 kN / cm2.Thus the average value of the weight loss bamboo rope the base that is equal to 8.0% smaller than in the bamboo Ampel the base is equal to 15.1%. While the average value of the weight loss bamboo rope central part that is equal to 12.6% smaller than in the central part of the bamboo Ampel of 14.0%. The average value of compressive strength greater than the bamboo rope bamboo Ampel. This is because the content of starch in the lower rope bamboo from bamboo Ampel. In terms of weight loss (weight) of bamboo seen that the entire sample to lose weight. This is mostly due to termite attack on bamboo. However, bamboo is not attacked by termites also experienced weight loss and can be caused by factors such as the weather (sun and rain) and mushrooms Keywords: study of bamboo, rope and ampel, termites attack